Study for Urban Dike-pond System on Non-point Pollution Control in Hydro-fluctuation Belt of the Hanfeng Lake - ZHANG Xin; CHEN Yaxian; ZHENG Yarong; XIAO Xing; WANG Yan; SUN Rong (Renmin Zhujiang)
Based on the wetland system of urban landscape dike-pond,and enhanced biological treatment of dike-pond by planting a variety of aquatic plants,this paper discusses the ability of multi-pond wetland system to reduce nitrogen,phosphorus,COD and other pollutants in urban surface runoff,and analyzes the concentration change of nitrogen,phosphorus,COD and other pollutants in urban surface along the lake.The results show that:Before and after rain,the multi-pond system has a better treatment effect on urban surface runoff;the larger the area and the higher the vegetation coverage,the better the treatment effect on surface runoff sewage.Both before and after the rain,artificially designed dike-ponds have higher pollutant removal efficiency than the natural dike-ponds.In overall,the wetland systems of urban landscape dike-pond have better treatment effect on surface runoff,the removal efficiency after rain is higher than that before rain,and TN,TP,NH+4-N,COD reduces along the lake.